Digital Fingerprinting In Encrypted Domain - Murala, Kranthi Kumar; Kamaraju, Dr.M.; Ramanjaneyulu, Dr.K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Digital fingerprinting is a method for protecting multimedia content from illegal redistribution and identified the colluders.In copy protection, a content seller embeds a unique identity as a watermark into the content before it is sold to a buyer. When an illegal copy is found, the seller can identify illegal users by extracting the fingerprint. In thisÂ  proposing an anonymous fingerprinting Â based on a homomorphic additive encryption scheme, it present a construction of anti-collision codes created using BIBD(Balanced incomplete block design) codes technique and dither technique which makes use of LFSR (linear feedback shift register) are used for improving the high robustness and Security.